Synergistic advancements: fostering collaborative excellence in doctoral education - Pelser, Anna-Marie (Frontiers in Education, 2024)
Doctoral education in Africa is a rigorous journey that demands unwavering commitment from both students and mentors. It involves original research aimed at contributing new knowledge to the academic realm, making it a formidable scholarly pursuit. The pivotal players in this endeavor are the students, their mentors, and the higher education institutions.This paper delves into the strategies and recommendations for enhancing excellence in doctoral education across Africa. One significant approach is fostering entrepreneurship among doctoral students, empowering them to develop businesses and cultivating an innovative culture to broaden their career prospects. Additionally, robust academic support systems play a crucial role, encompassing services like academic writing centers, article writing workshops, and well-structured mentoring programs. These resources bolster research and writing skills, aid in crafting research proposals, and facilitate publishing, thereby boosting students' self-esteem.International partnerships offer opportunities for academic mobility, through scholarships, exchange programs, and funding. This international exposure fosters cross-cultural understanding and academic excellence. Collaborations, both with academia and 2 industry, enable problem-solving and interdisciplinary research, further enriching the doctoral experience.Exchange programs serve dual purposes by providing funding and ensuring quality standards are met in doctoral programs. These measures collectively contribute to the advancement of excellence in doctoral education in Africa, nurturing a skilled workforce capable of driving innovation and development on the continent. This theoretical paper relies on extensive scrutiny of reputable sources and accredited journals. The findings emphasize the significance of collaborations and academic support systems in achieving academic success, which, in turn, leads to entrepreneurship, job creation, and wealth generation. Adequate funding and motivated supervisors and students are foundational elements for a thriving doctoral program. Overall, these interventions and recommendations pave the way for Africa's doctoral students to reach their full potential, contributing to the continent's growth and prosperity.